Peran Posyandu Dalam Meningkatkan Partisipasi Masyarakat Untuk Menjaga Kesehatan Anak Di Kelurahan Dauh-Puri Denpasar - Darmaputra, I Kadek Ari; Punia, I Nengah; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
This study looks at how Posyandu helps the community get involved in keeping children healthy in Dauh Puri Subdistrict, Denpasar. It also examines what encourages people to take part. The research is qualitative and includes interviews and observations with people connected to Posyandu in that area. The research uses the Participation Theory by Cohen and Uphoff. The findings show that Posyandu team members are very active in spreading information about family planning, giving advice on nutrition, providing immunizations, and helping with managing diarrhea. The success of Posyandu comes from the teamwork between the government, local leaders, the Posyandu team, and the community. Posyandu does more than just provide health services—it also helps bring about social change by encouraging people to take part actively. The study suggests that improving the facilities, infrastructure, and skills of Posyandu team members is important for providing better health care. Keywords: Posyandu, Community Participation, Child Health, Dauh Puri Subdistrict.